Effect of weathering on the geomechanical properties of the Miocene basalts in Malatya, Eastern Turkey - Gurocak, Z; Kilic, R (Springer Heidelberg, 2005)
Miocene volcanic rocks are widely exposed in the eastern Taurids, Turkey. The geomechanical properties and weathering degree of the Middle-Upper Miocene basalts were determined at the Boztepe dam site in Malatya, eastern Turkey. An engineering geology map of the Boztepe dam site was made and the joint sets and the degree of weathering determined in the field. The degree of weathering and RQD values were obtained on some 1,195 in of core which was then compared with a series of geomechanical tests including unit weight, porosity, water absorption, uniaxial compressive strength and compressive wave velocity. The geomechemical properties were compared with the weathering classifications of ISRM (Rock characterization, testing and monitoring, p 211, 1981) and Kilic (Environ Eng Geosci 4:475-483, 1999)
Keywords: basalt; Eastern Turkey; geomechanical properties; weathering